X-Ray microtomography (XMT) to observe penetration depth of high contrast bonding agent into sound dentine. (2019) - Mohd Kenali, N.; Davis, G.R.; Patel, M.
Abstract: This is a novel study on imaging of high contrast bonding agent penetration depth into dentine. A drop of each primer and sealer (Adper Scotchbond Multipurpose) was scanned with XMT. High contrast primer was developed by incorporation with iodine and tin methacrylate (SnM) respectively. A drop of each primer and sealer with contrast solution was scanned and the linear attenuation coefficient (LAC) from the XMT images was recorded. Four molar teeth were treated with 37% phosphoric acid. In group 1, the teeth were applied with primer incorporated with iodine and sealer incorporated with SnM. In Group 2, primer and sealer incorporated with SnM were used respectively. The penetration depth of primer was measured and sealing of dentine with sealer was observed in XMT images. Primer containing iodine showed penetration depth from 30-300µm in sound dentine but only 30-35µm penetration depth was found with primer added with SnM. Complete, homogenous sealing of dentine was found with sealer containing SnM. Primer with iodine suggests more penetration in tubules than primer with SnM.